2021
DOI: 10.3389/ijph.2021.591027
|View full text |Cite
|
Sign up to set email alerts
|

Public Preferences for Exit Strategies From COVID-19 Lockdown in Germany—A Discrete Choice Experiment

Abstract: Objectives: To decrease the rapid growth of SARS-CoV-2 in Germany, a stepped lockdown was conducted. Acceptance and compliance regarding entering and exiting lockdown measures are key for their success. The aim of the present study was to analyse the population's preferences for exiting lockdown measures.Methods: To evaluate population’s preferences and identify trade-offs between different exit strategies, a discrete choice experiment was conducted on 28–29 April (n = 1,020). Overall, six attributes and 16 ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 36 publications
2
23
0
Order By: Relevance
“…Little evidence is available on preferences around epidemic control measures [ 3 , 14 ], and this paper contributes to this emerging literature. The closest element in the literature is a DCE conducted in France at the end of the first lockdown, which focused on generally applicable measures such as wearing masks, travel limitation, and digital tracking [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Little evidence is available on preferences around epidemic control measures [ 3 , 14 ], and this paper contributes to this emerging literature. The closest element in the literature is a DCE conducted in France at the end of the first lockdown, which focused on generally applicable measures such as wearing masks, travel limitation, and digital tracking [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…A second approach is to directly account for individuals’ opinions and preferences, using preference elicitation tools such as stated preferences surveys [ 3 , 9 , 14 ]. The usefulness of this second approach relies on the assumption that the closer the measures are aligned with public preferences, the more sustainable and acceptable they will be for individuals and society.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The acceptability of tracing apps has shown mixed results in this review. A study in Germany [ 66 ], found that people preferred to avoid mandatory tracing apps during exit strategy, while a cross-country study [ 67 ] from France, Germany, Italy, the UK, and the US found strong support for use of apps.…”
Section: Resultsmentioning
confidence: 99%
“…DCEs have been increasingly applied in public health research to understand citizens' preferences with respect to interventions or programmes [17], and empirical research has demonstrated their robust external validity: for example, they have been used to accurately predict medical treatment [18] and vaccination behaviour [19]. During the pandemic, DCEs have been used to understand which vaccine characteristics are most in uential in decision-making [20]; health and economic trade-offs in lockdowns [21]; and exit strategies [22].…”
Section: Discrete Choice Experiments Designmentioning
confidence: 99%